Cultivation of Cassava (Manihot Esculentus C.) With Selected Legumes for Growth, Yield and Economic Advantages as Climate Change Mitigations (International Journal of Smart Agriculture, 2023)
Cassava (Manihot esculentus Crantz.) is a monoecious perennial shrub that is extensively cultivated as an annual crop in tropical and subtr++=opical regions for its edible, starchy, tuberous roots. It is ideal for intercropping with short-duration crops, which are often harvested before the cassava canopy closes. Thus, intercropping cassava, especially with legumes, is an important way for poor farmers to provide additional crop yield during the early growth stage. Moreover, the incorporation of legumes into cassava-based cropping systems may offer one of the most feasible ways of enhancing protein intake and nutritional security of farming households. Accordingly, a 1-year field study on cassava intercropped with three legumes (haricot bean, mung bean, and soybean) in southern Ethiopia was conducted to determine the effect of intercropping on the growth, yield, and economic advantage of the cassava. The experiment was laid out in a randomized complete block design (RCBD) with three replications. The results revealed that there were significant (P